Level and Correlates of Unmet Need of Contraception among Women in Extended Postpartum in Northern Ethiopia - Embafrash, Gurja; Mekonnen, Wubegzier (International Journal of Reproductive Medicine, 2019)
Background. About 222 million women in developing countries had unmet need for contraception. Women in their first year after childbirth had the largest proportion of unmet need for contraception. This first year after delivery is described as an extended postpartum period. Objective. To determine the level and correlates of unmet need for family planning among women who are in an extended postpartum period in the Tahtay Koraro District, Northern Ethiopia. Material and Method. A cross-sectional facility-based study complemented by in-depth interview of key informant was implemented. A total of 409 women in the 1st year after delivery were recruited. The study period was from 1st February to March 30, 2014. For quantitative data Epi-Info version 3.5.4 software was used for data entry, and then data were exported to SPSS Version 21 software for further analysis. Logistic regression model was used to identify factors associated with the outcome variable. The transcribed and translated qualitative text data were imported into an Open Code program and coded. Then codes were categorized and thematically described. Results. The overall unmet need for family planning was 150 (36.7%), with 121 (29.6%) for spacing and 29 (7.1%) for limiting. One hundred twenty (29.3%) women were using family planning and 94 (78.3%) of them were using injectable. The commonest reasons for nonuse of FP were nonmenstruating since last birth 201 (69.6%), side effects 39 (13.5%), and not having sex 25 (8.7%). Rural residence (AOR=7.16, 95% CI 2.57-19.95), postpartum week (26-38 weeks; AOR=8.16, 95% CI 4.24-15.71), and low perceived risk of pregnancy (AOR=1.79, 95% CI 1.04-3.09) were significantly associated with high unmet need. Opposition from different groups of the community, low perceived risk of pregnancy, provider refusal of removal of implants, and misunderstanding of FP use and side effects were additional triggering factors for unmet need. Conclusion and Recommendation. The unmet need for family planning was high. Rural residence, increased maternal postpartum week, and low perceived risk of pregnancy were associated with high unmet need. Opposition from different sects of the community and provider refusal of implant removal were also other factors triggering unmet need. Empowering women with knowledge of the risk of pregnancy and FP use during an extended postpartum period should be enhanced. Further awareness creation should be extended to periphery at different levels of the community.